Effects of Leucaena (Leucaena leucocephala) Silage as a Roughage Source on Digestibility and Growth Performance in Native Crossbred Sheep - Matukae, Bukhoree; Noolaong, Jarunee; Jeanmas, Arraya; Samaae, Maisaroh; Boonthep, Kettawan; Thongdonkham, Suwanna (YRU Journal of Science and Technology, 2025)
The use of low-cost and readily available local feed ingredients helps reduce production costs and enhances the sustainability of livestock farming. This study aimed to evaluate the effects of using Leucaena leucocephala silage as a roughage source on digestibility and growth performance in crossbred native sheep. The experiment was conducted using three weaned male crossbred native sheep with an average body weight of 17.17 ± 0.22 Kilogram and approximately 3 months of age. A 3 × 3 Latin square design was applied, in which each animal received three different experimental diets in separate periods as follows: Experimental diet 1 consisted of 100 Percent dried pangola grass (Digitaria eriantha) supplemented with concentrate. Experimental diet 2 contained 50 Percent dried pangola grass and 50 Percent Leucaena silage, also supplemented with concentrate. Experimental diet 3 consisted of 100 Percent Leucaena silage supplemented with concentrate. During the experimental period, the body weight of sheep was recorded at the beginning and end of the trial. Feed intake and fecal output were also measured. Samples of experimental diets and feces were collected for chemical composition analysis. All collected data were analyzed statistically. The results showed that using 50–100 Percent Leucaena silage as a roughage source for crossbred native sheep had no statistically significant effect (P>0.05) on digestibility and growth performance. However, a higher level of Leucaena silage in the diet significantly increased the intake of protein and lignin (P<0.05). Therefore, Leucaena should be used as both a protein source and a roughage source in combination with other low-lignin roughages. This approach may help reduce the amount of concentrate, excess protein, and lignin in the diet.